Design of Urban Rail Transit Operation Energy Saving Optimal Control Method - ZHANG Hongguang (机车电传动)
Urban rail transit system energy consumption is from vehicles traction, air-conditioners, elevators, water supply &drainage etc., and vehicles traction accounts more than 40% of the total energy consumption. So, maximized reduction of the vehicle traction energy consumption has become a growing concerned problem. Aiming at the vehicle operation control of complex line conditions, an optimal algorithm based on recursive thinking was designed, which could obtain optimal operation control scheme under specified time and line condition and effectively reduce the traction energy consumption. At the same time, cooperative control for maximized utilizing brake regeneration energy in multiple vehicles operation was researched, and some solvers were provided.